2016
DOI: 10.5194/acp-16-3033-2016
|View full text |Cite
|
Sign up to set email alerts
|

Brown carbon aerosols from burning of boreal peatlands: microphysical properties, emission factors, and implications for direct radiative forcing

Abstract: The surface air warming over the Arctic has been almost twice as much as the global average in recent decades. In this region, unprecedented amounts of smoldering peat fires have been identified as a major emission source of climate-warming agents. While much is known about greenhouse gas emissions from these fires, there is a knowledge gap on the nature of particulate emissions and their potential role in atmospheric warming. Here, we show that aerosols emitted from burning of Alaskan and Siberian peatlands a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
136
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 52 publications
12
136
0
Order By: Relevance
“…The range of E AbsDen at 405 nm observed in this study is similar to previous studies (McMeeking et al, 2014;Lack et al, 2012a), except for peat emissions where much higher absorption enhancement is observed. The peat burns give a very high value (5.65 ± 1.43) of E AbsDen at 405 nm because smoldering emissions from peat are predominantly BrC with a negligible amount of BC content (Chakrabarty et al, 2016;Pokhrel et al, 2016;Stockwell et al, 2016). It is evident from Fig.…”
Section: Absorption Enhancement Derived With a Thermal Denudermentioning
confidence: 58%
“…The range of E AbsDen at 405 nm observed in this study is similar to previous studies (McMeeking et al, 2014;Lack et al, 2012a), except for peat emissions where much higher absorption enhancement is observed. The peat burns give a very high value (5.65 ± 1.43) of E AbsDen at 405 nm because smoldering emissions from peat are predominantly BrC with a negligible amount of BC content (Chakrabarty et al, 2016;Pokhrel et al, 2016;Stockwell et al, 2016). It is evident from Fig.…”
Section: Absorption Enhancement Derived With a Thermal Denudermentioning
confidence: 58%
“…The absorption Ångström exponent (AAE) of BrC varies between 2 and 11, and the mass absorption coefficient of the water-insoluble fraction is generally much higher than that of the water-soluble fraction (Laskin et al, 2015). Smoldering combustion of peat yielded a variety of particles including spherical ones and agglomerates typically having a higher bulk oxygen-to-carbon ratio (Chakrabarty et al, 2016) than that reported by Pósfai et al (2004). These compositional differences likely resulted in a significantly higher Ångström exponent for the various particles formed in slow-burning processes at low temperature than that for laboratory-generated "pure" tar balls with a C / O ratio of about 10 and distinctive morphology (Hoffer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that OA components can contribute substantially to light absorption. In contrast to BC, which absorbs light throughout the UV-visible spectrum, an OA component such as brown carbon (BrC) absorbs mostly at the ultraviolet wavelengths and less significantly in the visible spectral range (Kirchstetter et al, 2004;Bergstrom et al, 2007;Chen and Bond, 2010;Zhong and Jang, 2014;Chakrabarty et al, 2016). The majority of BrC is emitted to the atmosphere through low temperature, incomplete combustion of biomass, bio-and fossil fuel (Bond, 2001;Kirchstetter et al, 2004;Bergstrom et al, 2007;Lewis et al, 2008;Chen and Bond, 2010;Zhong and Jang, 2014).…”
Section: Refractive Indexmentioning
confidence: 99%